(untitled) (International Journal of Biology and Chemistry, 2026)
A series of novel imidazole-containing α-aminophosponate derivatives were synthesized based on 1-(3-aminopropyl)imidazole using the absolute benzene under the one-pot, three-component Kabachnik–Fields reaction. The hematopoiesis-stimulating activity was evaluated for the compounds 7βCD-12βCD. The structure of the obtained compounds was confirmed using nuclear magnetic resonance (NMR) spectroscopy, infrared spectroscopy (IR), and elemental analysis. All tested compounds were β-cyclodextrin inclusion complexes of dialkyl(3-(1H-imidazol-1-yl)propylamino)(fluoro- and trifluoromethylphenyl)methyl)phosphonates to enhance aqueous solubility, improve bioavailability, and modulate the pharmacokinetic profile of the phosphonates. Among the tested derivatives, compounds 7βCD, 8βCD, 10βCD, and 11βCD exhibited low hematopoiesis-stimulating activity, whereas 9βCD and 12βCD demonstrated a moderate stimulatory effect on leukopoiesis. Biological evalution in a cyclophosphamide-induced pancytopenia model revealed that several complexes exhibit hematopoietic properties. Notably, 9βCD and 12βCD moderately stimulated leukopoiesis at a level comparable to methyluracil, significantly restoring the total leukocyte and lymphocyte counts and normalizing the Harkavy index. Despite their positive effects on leukopoiesis, compounds 9βCD and 12βCD showed limited influence on erythropoiesis and thrombopoiesis. In contrast, other derivatives (7βCD, 8βCD, 11βCD) did not exhibit stimulatory activity and, in some cases, even suppressed hematopoietic parameters. Taken together, these findings indicate that complexes of β-cyclodextrin with imidazole-containing α-aminophosphonates - particularly the complex of dimethyl(((3-(1H-imidazol-1-yl)propyl)amino)(4-fluorophenyl)methyl)phosphonate with β-cyclodextrin (9βCD) and complex of dimethyl ((3-(1H-imidazol-1-yl)propylamino)(4-(trifluoromethylphenyl)-methyl)phosphonate with β-cyclodextrin (12βCD) - represent promising scaffolds for the development of novel modulators of hematopoiesis. The observed biological activity may be associated with the presence of electron-withdrawing substituents (fluoro- and trifluoromethyl groups) and the imidazole fragment, which can contribute to intermolecular interactions with biological targets and participate in hydrogen bonding, facilitating binding to enzyme active sites, while the phosphonate moiety provides enhanced metabolic stability. Overall, these holdings suggest the potential of certain phosphonate derivatives, particularly 9βCD and 12βCD, as possible candidates for the further development of immunomodulating agents. Key words: hematopoiesis-stimulating activity; phosphonate derivatives; β-cyclodextrin inclusion complexes of dialkyl ((3-(1H-imidazol-1-yl)propylamino)(fluoro- and trifluoromethylphenyl)methyl)phosphonate.